The Effectiveness of Mindfulness-Based Cognitive Therapy on Life Enthusiasm and Psychological Hardiness in Female Heads of Households with Hypertension - Jafari, Zahra; Amoozad Mahdiraji, Mahboube; Haghighat, Atefeh; Radmehr, Maisa; Shamloo Sani, Shahrzad (Psychology of Woman Journal, 2024)
Objective: The aim of this study was to determine the effectiveness of mindfulness-based cognitive therapy on life enthusiasm and psychological hardiness in female heads of households with hypertension.Methods and Materials: The research method was quasi-experimental, employing a pretest-posttest control group design. The statistical population included female heads of households with hypertension who referred to health centers in District 4 of Tehran in 2022. From this population, 30 participants were selected using convenience sampling and randomly assigned to an experimental group (15 participants) and a control group (15 participants). In this study, questionnaires on life enthusiasm and psychological hardiness were utilized. The experimental group received eight 2-hour sessions of mindfulness-based cognitive therapy, while the control group did not receive any specific intervention. To assess the effectiveness of the mindfulness-based cognitive therapy, inferential statistics were employed, specifically univariate analysis of covariance (ANCOVA)Findings: The findings indicated that the mean scores of life enthusiasm and psychological hardiness in the posttest were significantly higher than those in the pretest for the experimental group.Conclusion: Therefore, mindfulness-based cognitive therapy affects life enthusiasm and psychological hardiness in female heads of households with hypertension.